Synthetic Cannabinoid‐Associated Multiple Organ Failure: Case Series and Literature Review. Issue 4 (27th March 2019) - Armstrong, Faith; McCurdy, Michael T.; Heavner, Mojdeh S.
Abstract : Objective: We describe a multicenter descriptive case series of six patients admitted with synthetic cannabinoid (SC) intoxication displaying similar symptoms and sequelae, all resulting in multiple organ failure. Methods: Patients were included in this report if they presented with known SC use and experienced multiple organ failure between March 1, 2016, and July 19, 2016, to the intensive care units of three hospitals in Maryland. Patients were followed to either discharge or death, and complications related to SC were documented. Results: All six patients presented with altered mental status and severe rhabdomyolysis, with a peak creatine phosphokinase ranging from 4000 to >320, 000 units/L. The majority of patients (five of six) presented with acute kidney injury, with most (four of six) requiring continuous renal replacement therapy. Most patients experienced fever (five of six) and myocardial injury, as evidenced by a troponin elevation (three of six). Seizures occurred in half of patients (three of six patients). Two patients required emergent fasciotomies of the bilateral lower extremities for acute compartment syndrome. Two patients developed fulminant hepatic failure that necessitated liver transplant evaluation, one requiring Molecular Adsorbent Recirculating System (MARS) therapy as a bridge to successful transplant, while the patient without it did not survive. Delirium, severe rhabdomyolysis, acute kidney injury, and fever are common in patients with synthetic cannabinoid intoxication. Conclusions: Given the growing abuse of these substances, clinicians should consider their use in the differential of such patient presentations. To our knowledge, only a few published case reports discuss multiple organ failure associated with SC toxicity, and only two have described an associated acute liver failure. Our report describes the first case of SC‐associated acute liver failure requiring organ transplantation. Clinicians should be aware of life‐threatening complications and consider SC ingestion in the differential diagnosis of patients presenting with multiple organ failure.